REducing unwarranted variation in the Delivery of high qUality hip fraCture services in England and Wales (REDUCE): protocol for a mixed-methods study. Issue 5 (19th May 2021) - Patel, Rita; Drew, Sarah; Johansen, Antony; Chesser, Tim; Javaid, Muhammad K; Griffin, Xavier L; Jones, Tim; Griffin, Jill; Bradshaw, Marianne; Whale, Katie; Barbosa, Estela Capelas; Marques, Elsa M R; et al.
Abstract : Introduction: Substantial variation in the delivery of hip fracture care, and patient outcomes persists between hospitals, despite established UK national standards and guidelines. Patients' outcomes are partly explained by patient-level risk factors, but it is hypothesised that organisational-level factors account for the persistence of unwarranted variation in outcomes. The mixed-methods REducing unwarranted variation in the Delivery of high qUality hip fraCture services in England and Wales (REDUCE) study, aims to determine key organisational factors to target to improve patient care. Methods and analysis: Quantitative analysis will assess the outcomes of patients treated at 172 hospitals in England and Wales (2016–2019) using National Hip Fracture Database data combined with English Hospital Episodes Statistics; Patient Episode Database for Wales; Civil Registration (deaths) and multiple organisational-level audits to characterise each service provider. Statistical analyses will identify which organisational factors explain variation in patient outcomes, and typify care pathways with high-quality consistent patient outcomes. Documentary analysis of 20 anonymised British Orthopaedic Association hospital-initiated peer-review reports, and qualitative interviews with staff from four diverse UK hospitals providing hip fracture care, will identify barriers and facilitators to care delivery. The COVID-19 pandemic has posed a major challenge to the resilience of services and interviews will explore strategies used to adapt and innovate. This system-wide understanding will inform the development, in partnership with key national stakeholders, of an 'Implementation Toolkit' to inform and improve commissioning and delivery of hip fracture services. Ethics and dissemination: This study was approved: quantitative study by London, City and East Research Ethics Committee (20/LO/0101); and qualitative study by Faculty of Health Sciences University of Bristol Research Ethics Committee (Ref: 108284), National Health Service (NHS) Health Research Authority (20/HRA/71) and each NHS Trust provided Research and Development approval. Findings will be disseminated through scientific conferences, peer-reviewed journals and online workshops.